Dietary fat content modulates the hypolipidemic effect of dietary inulin in rats - Han, Kyu‐Ho; Yamamoto, Aiko; Shimada, Ken‐ichiro; Kikuchi, Hiroto; Fukushima, Michihiro (Molecular nutrition & food research, 2017)
Scope Dietary fat content (low versus high fat) may modulate the serum lipid‐lowering effect of high‐performance (HP)‐inulin. This study investigated the effect of dietary HP‐inulin on metabolism in rats fed a low‐ or high‐fat diet. Methods and results Rats were fed a diet of 5% fat with 5% cellulose or 5% HP‐inulin (average degree of polymerization = 24) (low‐fat diet) or of 20% fat with 5% cellulose or 5% HP‐inulin (high‐fat diet) for 28 days. Total, HDL, and non‐HDL cholesterols, and triglyceride concentrations in the serum were measured along with total lipid content of liver and feces. Hepatic triglyceride and cholesterol, and fecal neutral and acidic sterol concentrations in total lipid were assessed. In addition, cecum SCFA levels and bacterial profiles were determined. The hypolipidemic effect of HP‐inulin differed depending on dietary fat content (5% versus 20%). Specifically, 5% inulin instead of cellulose in a semi‐purified diet significantly reduced serum lipid levels in rats fed a high‐fat diet, which was strongly associated with increased total lipid and neutral sterol excretion. Conclusion Dietary fat content modulates the hypolipidemic effect of dietary inulin. The hypolipidemic effect of inulin differs depending on dietary fat content (5 versus 20%). Specifically, 5% inulin instead of cellulose in a semi‐purified diet significantly reduces serum lipid levels in rats fed a high‐fat diet, which is strongly associated with increased total lipid and neutral sterol excretion. These results indicate that dietary fat content modulates the hypolipidemic effect of dietary inulin.